Restoration and Sustainable Development of Cambodia’s Cultural Heritage After 1979 Under the Khmer Rouge Aftermath - Tran Minh, Duc (Eco-Tourism and Sustainable Development, 2025)
This paper analyzes the process of restoring Cambodia’s cultural heritage in the aftermath of 1979, closely linking the rehabilitation of tangible monuments, the revival of intangible heritage, and the reconstruction of the social fabric. First, the author examines the devastation wrought by the Khmer Rouge regime on the Angkor complex, Buddhist temples, and courtly arts such as Apsara dance, alongside the pivotal restoration role played by the Royal Family and the international community. Next, the theoretical frameworks of “value interaction” and the “civilizing mission” are applied to evaluate the shift from pure conservation to sustainable development, integrating a strictly protected core zone with a community-based tourism buffer zone. The paper also elucidates the mechanisms for Buddhist reconstruction through architectural rehabilitation, monastic training, and national reconciliation rituals, while analyzing the cultural–religious tourism model linked to community development. International cooperation has been crucial in providing financial support, technical expertise, and digital technology transfer (Digital Angkor), laying the groundwork for local capacity building and expert networks (APSARA Authority). In the discussion, the author highlights notable achievements but also identifies challenges related to resource constraints, policy coherence, commercialization pressures, and climate change. Finally, the paper draws lessons for post-conflict heritage sites and proposes future research directions on the digitization of intangible heritage, green tourism, and integrated intersectoral policies.